2011
DOI: 10.1073/pnas.1110013108
|View full text |Cite
|
Sign up to set email alerts
|

Diameter and rigidity of multiwalled carbon nanotubes are critical factors in mesothelial injury and carcinogenesis

Abstract: Multiwalled carbon nanotubes (MWCNTs) have the potential for widespread applications in engineering and materials science. However, because of their needle-like shape and high durability, concerns have been raised that MWCNTs may induce asbestos-like pathogenicity. Although recent studies have demonstrated that MWCNTs induce various types of reactivities, the physicochemical features of MWCNTs that determine their cytotoxicity and carcinogenicity in mesothelial cells remain unclear. Here, we showed that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
452
7
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 460 publications
(505 citation statements)
references
References 47 publications
24
452
7
14
Order By: Relevance
“…Paraffin-embedded tissues were cut into 4 mm sections and subjected to hematoxylin and eosin (H&E) staining or Perls' iron staining. Determination of iron concentration by using inductively coupled plasma-mass spectrometry (ICP-MS) was done as previously described (25).…”
Section: Experiments To Determine Maximal Tolerated Level Of Iron-redmentioning
confidence: 99%
“…Paraffin-embedded tissues were cut into 4 mm sections and subjected to hematoxylin and eosin (H&E) staining or Perls' iron staining. Determination of iron concentration by using inductively coupled plasma-mass spectrometry (ICP-MS) was done as previously described (25).…”
Section: Experiments To Determine Maximal Tolerated Level Of Iron-redmentioning
confidence: 99%
“…[23,25] Furthermore, genotoxicity associated with CNTs-cellular exposure has been shown to lead to potential carcinogenic risks similar to ones found for asbestos. [26] Studies have shown that cancer development is related to alterations in cell mechanical phenotype including changes in the cell structure, [27] morphology, [28] and responses to mechanical stimuli. [29] The mechanical phenotype of cells is regulated by dynamic networks of cytoskeletal filaments (i.e., cellular scaffold) such as microtubule and actin, [30] and by signaling molecules.…”
mentioning
confidence: 99%
“…23 The animal experiment committee of Nagoya University Graduate School of Medicine approved this experiment.…”
Section: Animal Tissuesmentioning
confidence: 99%
“…21,22 We showed that the mesothelial endocytosis of crocidolite was accompanied by F-actin and Rab5a assembly. 23 Reportedly, fiber internalization increased once the fiber was coated with vitronectin, and integrin avb5 was suggested to be a receptor for vitronectin-coated crocidolite 24,25 and chrysotile. 26 However, even in those studies, a significant amount of asbestos fibers entered the cells in the absence of serum.…”
mentioning
confidence: 99%